A Review of Famciclovir in the Management of Genital Herpes - S. Faro (Hindawi Limited, 1998)
The frequent occurrence of genital herpes continues to be a serious clinical problem. Although not life threatening, the physical symptoms of the disease, and the ensuing psychosocial complications, can be overwhelming to patients. The life cycle of the herpes simplex virus is complex, comprising multiple stages. Following infection, the virus establishes life-long latency in its host and can reactivate at any time as a recurrent infection. Successful management of genital herpes simplex infections involves patient education and psychological support, as well as antiviral agents. The antiviral agent famciclovir has been shown to shorten the course and decrease the severity of episodes of recurrent genital herpes. In addition, famciclovir has been shown to be effective in suppressing recurrent genital herpes. A review of the clinical experience with famciclovir in the treatment of genital herpes is presented.